Persepsi Siswa terhadap Metode Al-Husna dalam Pembelajaran Al-Quran di SD Muhammadiyah Program Khusus Andong Boyolali Tahun 2016 - Lestari, Winda Ayu; , Dr. Mohamad Ali, M.Pd (2016)
Perception is the process of observation of a person against an object and situation objectively with the help of the senses. Without the correct perception, humans are impossible to capture and interpret a variety of information that is always around him. In the world of education, teachers' method is a technique in presenting the material that the students are able to absorb and understand easily. Selection of appropriate learning methods will excite student learning. SD Muhammadiyah PK (Special Program) Andong as an educational institution based on Islam, requires that all students are able to read the Qur'an properly. The method used is the method of Al-Husna. Before using Al-Husna, teachers use method Iqra that are considered effective in learning. However, after several years of application, students' skills in reading Hijaiyah letters have not maximized. Then, the teacher replace this method with method of Al-Husna, where the Hijaiyah letters that have the same characteristics and form combined. The results are students are able to read the Hijaiyah letters properly, quickly, and smoothly. Based on this background, the purpose of this study is to describe the students' perception on Al-Husna method of learning the Quran. This research is a field one that is carried out in certain school environments by visiting the direct target object. The methods used in gathering data are observation, documentation, and in-depth interview. While the method of data analysis is done in a descriptive way, that discloses the circumstances as they are. From the results of this study, it is concluded that students' perceptions on Al-Husna method of learning the Qur'an are very well. All students give positive response to the use of such methods. They are happy and love with the methods of Al-Husna, and they focus on learning the methods of Al-Husna, and so more easily understand the material by the method of Al-Husna. Keyword : Perception, Al-Husna Method, Elementary Students